Analysis of Internal Boiler Water Treatment Maintenance System on Boiler Operation in KM. Bukit Raya - Irfan, Saiful; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Boilers are auxiliary machines on ships that are usually used to produce pressurised steam that is needed on ships, namely for heating fuel, lubricating oil, and heating water for accommodation and machinery. In the operation of boilers on ships, it is determined by the quality of water to produce good boiler performance. The purpose of this research is to analyse the boiler water treatment system to determine the quality of ship boiler water using water quality testing standards based on the American Society Mechanical Engineer (ASME). Standard parameters set by ASME are pH and conductivity measurements, Alkalinity measurements, Hardness measurements, Silica and iron measurements in ship boiler water KM. Bukit Raya. From the results of the analysis of boiler water taken from sampling feed water boilers on ships KM. Bukit Raya shows the results of the analysis of boiler water on pH with the measured pH value still in the standard set by ASME, namely 10.5-11.5, boiler water analysis of hydrate alkalinity in samples 1,2,4 is still within ASME standards 200 - 400 ppm while the measurement of hydrate alkalinity exceeds the standard set by ASME of 420 ppm, excessive hydrate alkalinity will cause scale formation, boiler water to calcium obtained for samples 1-3 still meet ASME standards, namely trace, analysis of boiler water to Magnesium obtained for samples 1-3 still meet ASME standards, namely trace, analysis of boiler water to silica obtained silica measurements are still within the standards set by ASME 150 max